FRAMING FAITH AND LANGUAGE: A CRITICAL DISCOURSE ANALYSIS OF SOCIO-RELIGIOUS ETYMOLOGIES IN INDONESIAN LEXICOGRAPHY - Alnizar, Fariz; Mufidah, Vika Nurul; Yani, Zulkarnain (LLT Journal: A Journal on Language and Language Teaching, 2025)
A dictionary is more than a collection of words; it is a realm of knowledge and power where language, history, and ideology meet. This research aims to explore the representation and absence of etymological traces of socio-religious terms, particularly those of Arabic origin, in the online edition of the Kamus Besar Bahasa Indonesia (KBBI). A critical analysis of several entries shows that although since 2018 the KBBI has started to include etymological notes for some Arabic-derived words, this move remains partial, inconsistent and problematic. Terms such as modin and muslihat appear with superficial or distorted etymological explanations, while important terms in Islamic discourse such as istirjāʻ, tayamum, and barakah are missing. On the other hand, the inclusion of sectarian terms-such as Ahlussunnah, Khawarij, and Wahabi-indicates an epistemological bias as well as a reflection of the particular ideological framework at work in the compilation of the dictionary. These findings show that the KBBI is not entirely neutral as a linguistic archive, but rather a discursive arena that produces and reproduces meanings in Indonesia's socio-political landscape. Thus, the dictionary does not only function as a linguistic tool, but also a field of cultural and ideological attraction, where the authority to define language becomes a contested political issue.